2020
DOI: 10.1136/jech-2019-213159
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation matters: understanding associations between neighbourhood deprivation, unhealthy food outlets, unhealthy dietary behaviours and child body size using structural equation modelling

Abstract: Background Children residing in neighbourhoods of high deprivation are more likely to have poorer health, including excess body size. While the availability of unhealthy food outlets are increasingly considered important for excess child body size, less is known about how neighbourhood deprivation, unhealthy food outlets and unhealthy dietary behaviours are interlinked. Methods This study involves children aged 8-13 years (n=1029) and resided in Auckland, New Zealand. Unhealthy dietary behaviours (frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…It is likely the neighbourhood nutrition environment may relate to both nutrition behaviours and metabolic health [32,59]. Increased access to suboptimal nutrition environments (e.g., through increased pedestrian connectivity) may encourage unhealthy nutrition behaviours, ultimately leading to increased metabolic risk [60]. On the other hand, greater FFM can exist in the presence of other metabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely the neighbourhood nutrition environment may relate to both nutrition behaviours and metabolic health [32,59]. Increased access to suboptimal nutrition environments (e.g., through increased pedestrian connectivity) may encourage unhealthy nutrition behaviours, ultimately leading to increased metabolic risk [60]. On the other hand, greater FFM can exist in the presence of other metabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A further study from New Zealand investigated the association between neighborhood deprivation, unhealthy food outlets, unhealthy dietary behaviors, and children's weight status. The authors concluded that the neighborhood availability of unhealthy food outlets was not associated with children's weight status; however, high deprivation index and unhealthy dietary intake were positively associated with higher body weight in children [22].…”
Section: Introductionmentioning
confidence: 98%
“…The measurements investigated 10 key indicators from the 2006, 2011, and 2016 censuses and included, for example, the proportion of skilled professionals, education levels, employment levels, and single-parent households found in an area [21]. Studies have shown that children living in highly deprived areas are more likely to have unhealthy dietary behaviors, higher screen time, and, consequently, to be at higher risk of overweight or obesity compared to children living in areas of low deprivation [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the volume of fast food restaurants (but not proximity to the closest) was associated with higher risk of obesity in a study with over 30,000 youth in the United Kingdom [ 13 ]. One study in Aotearoa New Zealand (henceforth referred to as Aotearoa) revealed no direct relationship between unhealthy food environments and unhealthy dietary behaviours or excess body size using structural equation modelling [ 14 ]. Instead, greater neighbourhood deprivation and unhealthy dietary behaviours were both significantly related to having a higher waist-to-height ratio, which has been shown to be a useful predictor of metabolic syndrome in children [ 15 ].…”
Section: Introductionmentioning
confidence: 99%